tert.-Butylation of Toluene: A Statistical Study - Ismail, Mohammad; Hanif, Mohammad Abu; Galib, Mirza; Saha, Manoranjan (Bangladesh Journal of Scientific and Industrial Research, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> A statistical model was developed for the alkylation of toluene with tert.-butyl chloride in presence of anhydrous aluminum chloride as catalyst. Temperature, molar ratio of toluene to tert.-butyl chloride and amount of anhydrous aluminum chloride were chosen for investigation. A set of trials was planned according to a 3 factor 2-level Yates pattern experimental design with 2 replicates and the center point trial with 4 replicates. The critical response was the yield of tert.-butyl toluene. Two- and three-factor interaction effects together with the main effects were statistically significant. The adequacy of the suggested model was checked up. The difference between the experimental and predicted yields did not exceed 2.22%. The best yield of the tert.-butyl toluene was 51.2%. Key words: tert. Butylation, Yates pattern, Experimental yield, Statistical model. Â Â Â doi: 10.3329/bjsir.v43i4.2245 Bangladesh J. Sci. Ind. Res. 43(4), 545-552, 2008